A comparison of experiences and preferences regarding classroom and tutoring feedback among Chinese and Saudi learners of English - Wang, Xinran (Kansas State University, 2016)
This report studies ESL tutoring feedback to Chinese and Saudi students. The objective is to research the reasons of feedback differences and similarities, which include previous and current English learning styles, habits, purposes for receiving tutoring, and evaluations of tutors. Faced with L2 learners who come from different cultural backgrounds, it is helpful for instructors and tutors to know L2 students’ previous English learning experiences in their home countries so that instructors and tutors can adjust teaching or tutoring for each student. In addition, students who speak the same L1 have common problems of English learning due to their L1. In this way, ESL tutors not only tutor English skills, but also promote cultural awareness. Meanwhile, knowing students’ cultural background is necessary to give tutoring for each L2 learner. The present study aims to explore L2 learners’ feedback from previous and current English learning experiences and will help L2 instructors and tutors to know some basic knowledge about two different language groups.
Keywords: ESL tutoring; Comparision; Chinese; Saudi; L2 learners; Feedback